2021
DOI: 10.3390/biomedicines10010085
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Nanotherapeutic Approaches for Inflammatory Bowel Disease

Abstract: Oxidative stress, caused by the accumulation of reactive species, is associated with the initiation and progress of inflammatory bowel disease (IBD). The investigation of antioxidants to target overexpressed reactive species and modulate oxidant stress pathways becomes an important therapeutic option. Nowadays, antioxidative nanotechnology has emerged as a novel strategy. The nanocarriers have shown many advantages in comparison with conventional antioxidants, owing to their on-site accumulation, stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 110 publications
0
6
0
1
Order By: Relevance
“…Numerous pieces of evidence suggest that IBD is linked to the increased production of reactive species [ 56 ]. Oxidative stress not only directly disrupts the intestinal barrier, which leads to cell dysfunction and tissue damage in the colon, but also causes dysregulation of multiple cell types, such as intestinal epithelial cells and immune cells [ 56 , 57 ]. To determine the impact of CMC-AXT-NPs on oxidative stress in mice with UC, the levels of oxidative stress markers were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous pieces of evidence suggest that IBD is linked to the increased production of reactive species [ 56 ]. Oxidative stress not only directly disrupts the intestinal barrier, which leads to cell dysfunction and tissue damage in the colon, but also causes dysregulation of multiple cell types, such as intestinal epithelial cells and immune cells [ 56 , 57 ]. To determine the impact of CMC-AXT-NPs on oxidative stress in mice with UC, the levels of oxidative stress markers were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, P. distasonis possesses catalase and oxidative stress tolerance genes such as KatE gene and the OxyR gene ( Ezeji et al, 2021 ). Oxidative stress is associated with the initiation and progress of IBD while catalase is an important factor in oxidative stress tolerance ( Knaus et al, 2017 ; Liu et al, 2021 ). While DNA transcription, protein translation, biosynthesis, and spore-forming are accounted for a large proportion of functional annotation in the downregulated species at the remission stage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the efficacy of phytochemicals against TLR4-mediated inflammation ( Figure 1 ) ( 137 , 138 ). Flavonoids such as quercetin, catechin, and silymarin have proven therapeutic efficacy in the treatment of IBD ( Figure 3 ) ( 139 , 140 ). Here, they operate as effective antioxidants and cellular modulators of the protein kinase and lipid kinase signaling pathways that drive chronic intestinal inflammation ( 139 , 140 ).…”
Section: Role Of Antioxidants For Ibd-related Therapeutic Application...mentioning
confidence: 99%
“…Flavonoids such as quercetin, catechin, and silymarin have proven therapeutic efficacy in the treatment of IBD ( Figure 3 ) ( 139 , 140 ). Here, they operate as effective antioxidants and cellular modulators of the protein kinase and lipid kinase signaling pathways that drive chronic intestinal inflammation ( 139 , 140 ). Dogs with idiopathic IBD also have up-regulated activity of the JAK/STAT pathway marked by phosphorylated STAT3 (pSTAT3) overexpression ( 141 ).…”
Section: Role Of Antioxidants For Ibd-related Therapeutic Application...mentioning
confidence: 99%